The Comparative of Media Framing in 2019 Presidential Election Campaign - Tri Nugraha SAKTI; Alo LILIWERI; Mirza RONDA (International Journal of Environmental, Sustainability, and Social Science, 2023)
As is common knowledge, the euphoria of the election from one period to the next is a breath of fresh airfor the mass media crews to favor each other when reporting on events surrounding the campaign, includingthe presidential election. The fact information is worth selling, and a news report that is eagerly anticipatedby the public because it is a way of addressing the demand for information on the requirements of the peopleon specific people or groups of people who become newsworthy. National newspapers have a significantrole in establishing the reality of the campaign coverage of each Presidential Candidate (Capres). Theobjective of this research is to examine how Republika and Media Indonesia newspapers framing theircoverage of the 2019 Presidential Election Campaign between Joko Widodo and Prabowo Subianto throughnews articles published from 15 March to 31 March 2019. The method utilized in this study is qualitativeapprove a constructivist paradigm. The utilized theory is framing with the Zhong Dang and Pan Kosickimodel. The results demonstrated that there were ideological differences between Republika and MediaIndonesia, despite the fact that the ideology, editorial content, and ownership of the Republika newspaperdid not change during the 2019 presidential election campaign, when Mr. Eric Tohir was named campaignchairman for the presidential clone Joko Widodo. There appears to have been a shift in the delivery andframing of Joko Widodo's campaign coverage since 2014. And secondly, the prestige of political leaders.